A Generic Switching State-Space Model for Modular Multilevel Cascade Converters - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper presents a generic switching state-space model for modular multilevel cascade converters in double-star connection (MMCC-DS) which can either be used with chopper cells (CC; half bridges) or bridge cells (BC; full bridges) and allows to consider arbitrary switch(ing) faults. The output terminals of the MMCC-DS are connected to a general resistive-inductive (RL) load with additional voltage sources in star connection. The model is derived and described in detail by using Kirchhoff s current and voltage laws (KCL, KVL) and allows for currents flowing through the anti-parallel diodes of the active switches in each cell. The model is implemented in Matlab/Simulink 2019b and PLECS for a simulative validation and comparison of the proposed model. © 2020 IEEE.